Rotavirus and other viruses in the stool of premature babies - Van Renterghem, L. (J Med Virol, 2005)
In a 12‐month study, 363 stools of 199 premature babies nursed in a separate ward of a paediatric clinic were examined by electron microscopy and on cell culture to detect virus. Twenty‐four (6.6%) were positive for rotavirus, in one winter epidemy. From four stools Echo 22 was isolated, and in six cases virus‐like particles were detected by electron microscopy. These virus infections are not a major problem in newborns, requiring special care, as they are mostly symptomless or mild.